Understanding Integrated Environmental Assessment in a Multi-Stakeholder Negotiation via Role-Play. (February 2014) - Kim, Dong-Young
This article explains how a role-play game (RPG) can allow participants to get insights on the dynamics of incorporating scientific advice into adversarial policymaking. A RPG called GROUND-LEVEL OZONE (GLO) simulates a multi-stakeholder negotiation based on the recommendations of an integrated environmental assessment (IEA) for urban air quality management. Structured debriefing of the RPG used questionnaire survey of participants' perceptions of IEA usefulness as well as participants' feedback about the use of the IEA and performance of the facilitators during negotiations. By linking those perceptional and behavioral patterns to the negotiated outcomes, the debriefing drew much broader insights on the importance of upstream engagement for enhanced legitimacy of the IEA and constructive roles of a facilitator in a multi-stakeholder negotiation. This article also critically reviews the debriefing method and suggests a new design of more sophisticated debriefing method and a new RPG for more effective learning of the dynamics of the use of IEA in a multi-stakeholder negotiation in the future.